Seasonal Variations in Estradiol-17J3, Progesterone and Cortisol levels during estrous cycle in Buffaloes - SINGH, J K; LUDRI, R S; PANDITA, SUJATA (The Indian Journal of Animal Reproduction, 2023)
Variations in cyclic concentrations of Estradiol-l 7J3, Progesterone and Cortisol were determined by RIAfor_ one cycle each in five normal cycling buffaloes during summer, winter and rainy seasons. Overall meanvalues of progesterone were maximum in cold, followed by hot humid and warm seasons, with significant (P
Keywords: Estradiol-17beta; Progesterone; Cortisol; Estrous; Buffaloes